DETERMINAN KINERJA BIAYA DAN WAKTU PROYEK KONSTRUKSI DI INDONESIA DITINJAU DALAM KONTEKS ISLAMI - Rendy Mirwan Aspirandi; Akbar Maulana; Ivandra Argya Putra; Ahmad Iqbal Maulana (Universitas Muhammadiyah Jember, 2023)
This study analyzes the cost and time performance determinants faced by construction companies in Indonesia. This research is considered very important because there are still variations in the results of previous studies that found the determinants of cost and time performance of construction projects. This research is based on Theory of Performance (ToP) developing and connecting six basic concepts to form a framework that can be used to explain performance and performance improvement. The current level of performance depends holistically on 6 components, namely: context, knowledge level, skill level, identity level, personal factors, and fixed factors. The population and research sample are construction companies in Indonesia with a sampling technique, namely Random Sampling. The research method used is Quantitative Research with multiple linear regression analysis techniques. Variables that affect construction costs are External Complexity (X1), Quality Management (X9), and Construction Resource Management (X11). Variables that affect construction costs and time are Construction Method variables (X12). External complexity, quality management and construction resource management will affect the level of construction costs because the high or low of these three variables will change the structure of the initial budget plan. Construction methods that are getting better in a project will further increase the construction costs that must be incurred, because the construction method is related to how to carry out the construction of a construction, whether using sophisticated tools or simple tools. Likewise, the Construction Method has a significant effect on Construction Time (Y2). This is because when the Construction Method is improved in carrying out the project, the project completion time will also be longer, so that the completion time will be affected by the complexity or simplicity of the construction implementation method.